Think Beyond Particle Cytotoxicity: When Self-Cellular Components Released After Immunogenic Cell Death Explain Chronic Disease Development - Leinardi, Riccardo; Longo Sanchez-Calero, Chiara; Huaux, François (Frontiers in Toxicology, 2022)
The prolonged perturbation of the immune system following the release of a plethora of self-molecules (known as damage-associated molecular patterns, DAMPs) by stressed or dying cells triggers acute and chronic pathological responses. DAMPs are commonly released after plasma membrane damage or complete rupture due to immunogenic cell death (ICD), upon numerous stressors including infectious and toxic agents. The set of DAMPs released after ICD include mature proinflammatory cytokines and alarmins, but also polymeric macromolecules. These self-intracellular components are recognized by injured and healthy surrounding cells via innate receptors, and induce upregulation of stress-response mechanisms, including inflammation. In this review, by overstepping the simple toxicological evaluation, we apply ICD and DAMP concepts to silica cytotoxicity, providing new insights on the mechanisms driving the progress and/or the exacerbation of certain SiO2–related pathologies. Finally, by proposing self-DNA as new crucial DAMP, we aim to pave the way for the development of innovative and easy-to-perform predictive tests to better identify the hazard of fine and ultrafine silica particles. Importantly, such mechanisms could be extended to nano/micro plastics and diesel particles, providing strategic advice and reports on their health issues.